Pemodelan Aliran Sungai Jatiroto Menggunakan Software HEC-RAS 5.0.7 - Arimbi, Rovita Yuniarti; Sumiadi, Sumiadi; Winarta, Bambang (Fakultas Teknik, Universitas Brawijaya, 2022)
The Jatiroto River area, which is located on the border of Lumajang Regency and Jember Regency, is often hit by floods when the rainy season arrives. In 2022, floods hit the lower reaches of the Jatiroto River with an average water level of 30-50 cm. The influence of backwater from the Bondoyudo River downstream and discharge shipments from tributaries makes the cross-sectional capacity of the Jatiroto River unable to accommodate the incoming water discharge. The purpose of this flow modeling is to determine the point of the river section that occurs runoff so that it can be used as a recommendation for flood disaster prevention and mitigation plans.Â Calibration of flow modeling to determine n Manning using observational discharge in the weir and historical data of flooding on December 23, 2018. The results of the flow simulation using HEC-RAS 5.0.7 obtained n Manning values of 0.025 and 0.023. The planned flood discharge used for modeling analysis of existing conditions is Q2th of 373.10 m3/sec. From the results of the simulation of the flow of existing conditions in Q2th that in some river sections there was an overflow of water, especially the downstream section.Wilayah Sungai Jatiroto yang terletak di perbatasan Kabupaten Lumajang dan Kabupaten Jember sering diterjang banjir ketika musim penghujan tiba. Tahun 2022 kejadian banjir menerjang wilayah bagian hilir Sungai Jatiroto dengan ketinggian air rata-rata 30-50 cm. Adanya pengaruh backwater dari Sungai Bondoyudo di bagian hilir dan kiriman debit dari anak sungai membuat kapasitas penampang Sungai Jatiroto tidak dapat menampung debit air yang masuk. Tujuan dari pemodelan aliran ini untuk mengetahui titik ruas sungai yang terjadi limpasan sehingga dapat dijadikan rekomendasi rencana pencegahan dan mitigasi bencana banjir. Kalibrasi pemodelan aliran untuk menentukan n Manning menggunakan debit pengamatan di bendung dan data historis banjir pada tanggal 23 Desember 2018. Hasil dari simulasi aliran menggunakan HEC-RAS 5.0.7 didapatkan nilai n Manning sebesar 0,025 dan 0,023. Debit banjir rencana yang digunakan untuk analisis pemodelan kondisi eksisting yaitu Q2th sebesarÂ 373,10 m3/det. Dari hasil simulasi aliran kondisi eksisting Q2th bahwasanya di beberapa ruas sungai terjadi luapan air terutama ruas bagian hilir.